Poder coordenador e coordenação dos poderes, um exercício de história dos conceitos: de Alberto Torres à Constituição de 1934 - Allysson Eduardo Botelho de Oliveira (2022)
The object of this research is the semantic history of the concepts of coordinating power and coordination of powers. It is, therefore, a historical-legal research. Structured from the theoretical-methodological axis of the History of Concepts, by Reinhart Koselleck, the general objective of this research is to investigate the semantic continuities and discontinuities that characterized these concepts in the period that extends from the proclamation of the Republic, in 1889, to the promulgation of the 1934 Constitution. Thus, it was investigated (1) how these concepts were used by newspapers and books during the First Republic; (2) how the concept of coordinating power is outlined in the work of Alberto Torres; (3) how the concepts studied were used in the years that preceded the Constitution of 1934 (1931-1934), analyzing the newspapers and publications of this period, as well as the program of constitutional revision elaborated by Oliveira Vianna at the request of Juarez Távora, and the debates held in the Itamaraty Subcommittee; (4) how the terms coordinating power and coordinating powers were used in the constituent debates of 1933-1934. It was concluded that throughout the analyzed period (1889-1934), the concepts of coordinating power and coordination of powers underwent semantic changes, harboring different ranges of meaning. In this time lapse, such concepts were weapons and objects of political and semantic disputes, stressing the space of experience of the First Republic from a horizon of expectations that advocated the construction of a new institutional arrangement, with the creation of a Coordinating Power, which would be responsible for coordinating the powers.